The European Union Trust Fund for Africa: a glimpse of the future for EU development cooperation - Clare Castillejo (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The EU Emergency Trust Fund for stability and addressing the root causes of irregular migration and displaced persons in Africa (EUTF) was launched one year ago. This paper examines how the EUTF has developed during its first year and the extent to which initial expectations and concerns regarding the trust fund are proving valid. It begins by examining the aims of the EUTF, identifying the different aspirations for the fund held by different actors and the extent to which it is likely to deliver on these. It also explores tensions around the financing and governance of the EUTF and the extent to which African partners have been involved in the trust fund. The paper goes on to look at the EUTF's projects. These have so far had a relatively traditional development focus, although more migration management projects are now being planned. The paper identifies serious flaws with the project selection process and argues that these result in a choice of projects and implementers that are not necessarily the best fit for the trust fund's goals or for local needs. The paper stresses that effective implementation of the EUTF will require drawing on existing knowledge and undertaking monitoring, evaluation and learning at multiple levels. The paper discusses where the trust fund can add value to existing EU instruments: in speed, flexibility, and the potential for innovation. In particular, the EUTF could offer an opportunity for experimentation on some of the complex issues it seeks to address, and contribute to the development of knowledge about `what works' in this area. However, seizing this opportunity requires facilitating ongoing learning and adaptation; ensuring greater involvement of local actors; and persuading implementers to move away from `business as usual' models.The paper explores how the trust fund relates to existing EU commitments, strategies and instruments. It examines the central role that the EUTF plays in the EU's response to migration, as well as how the trust fund relates to both EU development and human rights commitments. Finally, the paper suggests that the trust fund may be an indication of emerging trends in EU development cooperation, particularly in its more streamlined procedures, less emphasis on partnership, close links to EU interests, and use of conditionalities. The paper concludes by arguing that the governance and management of the EUTF must be strengthened in order to seize the opportunities that it offers. However, it suggests that the trust fund throws up broader concerns about the direction of EU aid that cannot be easily assuaged and do not bode well for a future European cooperation based on development principles. Clare Castillejo is a Research Associate at the Overseas Development Institute. She is a specialist in governance and rights in fragile states, with a particular interest in inclusive peacebuilding and statebuilding.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik